Piloting a digitally-mediated social story intervention for autistic children led by teachers within naturalistic school settings. (July 2020) - Smith, E.; Toms, P.; Constantin, A.; Johnson, H.; Harding, E.; Brosnan, M.
Highlights: The first study to explore digital technology supporting the fidelity of social story interventions by teachers within a school setting. A new assessment framework was developed to enable a measure of social story treatment fidelity according to Gray's 10 Criteria. Findings demonstrated that with digital support teachers were able to complete social story interventions to a high degree of fidelity with autistic children within school settings. After a 4-week intervention period, the digital social stories were found to have significantly improved the behaviour, understanding and anxiety of autistic children, based on teacher perception. Such technology and fidelity measures can now be used within larger, controlled studies, to better explore the impact of child and intervention factors on the effectiveness of social story interventions. Abstract: Background: Social stories (SS) are widely used within the autism community. However, research into their effectiveness is mixed at best and mainly relies on single case study designs. Additional support from the researcher is also often provided, raising questions as to the use and effectiveness of SS within usual school settings. Method: Seventeen school teachers developed and delivered personalised digitally-mediated SS with 22 autistic children (aged 5-11yrs) over a 4-week intervention period. Data was collected during a baseline period (1 week), throughout the 4-week intervention phase and at 6-week follow-up to consider changes in child behaviour, understanding and anxiety. A new assessment framework to evaluation treatment fidelity according to Gray's 10 Criteria was also developed. Results: With the support of a new SS app teachers were able to carry out SS interventions with a high degree of fidelity within their usual school settings. Behavioural data showed significant improvements from baseline to week 4 for all measures relating to the goals of the intervention (including a reduction in anxiety and an increase in understanding), some of which were still present at follow-up. Conclusion: This study has demonstrated that technology can be used to support teachers to develop and deliver SS interventions to autistic children within school settings. Such technology can now be used to facilitate much needed future, larger, controlled studies within this area. Implications for practice are discussed.